Inspection and maintenance to reduce emissions of in–use cars: an overview in the European context. (4th August 2014) - Samaras, Z.
This paper gives an overview of a project, sponsored by the European Commission, that examines a periodic inspection and maintenance system for application at the European level. It discusses the basic technical issues underlying such a system, focusing on the available options of short tests. In a European context, with given differences between Member States, it is worthwhile to implement a system that could offer the potential users the possibility either to select among a number of proposed solutions the one that will be the most suitable for its case, and/or to use various different approaches, depending on the particular conditions.